DNA barcodes highlight genetic diversity patterns in rodents from lowland desert and Andean areas in Argentina. (8th March 2022) - Ojeda, Agustina Alejandra; Novillo, Agustina; Lanzone, Cecilia; Rodríguez, María Daniela; Cuevas, Maria Fernanda; Jayat, Jorge Pablo; Teta, Pablo; Ojeda, Ricardo Alberto; Borisenko, Alex
Abstract: Rodents are an important component of South America fauna. Their high diversity has motivated researchers to continually review their taxonomy, genetic diversity, species limits, and phylogenetic relationships. Here, we applied DNA‐barcodes for assessing the taxonomic and genetic diversity in the two major lineages of South American rodents: caviomorphs and sigmodontines. We analysed 335 COI barcodes in 34 morphologically determined species from 39 localities along central Andes and arid lands of Argentina. Neighbour‐joining and maximum likelihood reconstruction provided clear separation between species. The Barcode Index number and Bayesian Poisson tree processes were used to confirm concordance between sequence clusters and species designations by taxonomy. We found deep divergence within the Phyllotis xanthopygus species complex, with distances up to 13.0% between geographically separated lineages. Minor divergences (3.30% and 2.52%) were found within Abrothrix hirta, and Tympanoctomys barrerae, respectively, with differentiation in their genetic lineages. Also, we documented geographically separated clusters for Akodon spegazzinii and A. oenos with up to 2.3% divergence, but clustering methods failed to distinguish them as different species. Sequence results show a clear barcode gap with a mean intraspecific divergence (0.56%) versus a minimum nearest‐neighbour distance averaging (10.1%). Distances between congeneric species varied from 4.1 to 14%, with the exception of two related forms within Euneomys and the sister species Akodon spegazzinii and A. oenos . This study constitutes a substantial contribution to the global barcode reference library. It provides insights into the complex phylogeographic patterns and speciation scenarios in rodents, while highlighting areas that require in‐depth taxonomic and integrative research.